Feasibility, satisfaction, and goal attainment in routine telemedicine consultation in child and adolescent psychiatry and psychotherapy - Döpfner, Manfred; Wirth, Elena von; Adam, Julia; Goldbeck, Carolina; Schulze-Husmann, Karen; Herpertz-Dahlmann, Beate; Simons, Michael; Heuer, Fabiola; Schwendowius, Jan; Poustka, Luise; Wegner, Christiane; Bender, Stephan (European child & adolescent psychiatry, 2024)
Telehealth services were rapidly adopted during the COVID-19 pandemic, but evidence regarding the effectiveness and feasibility of telehealth services in child and adolescent mental healthcare is sparse. This study aims to investigate feasibility, satisfaction, and goal attainment in video-delivered consultations in routine care child and adolescent psychiatry and psychotherapy. A total of 1046 patients from four university child and adolescent outpatient psychiatric clinics and one university outpatient unit for child and adolescent psychotherapy were screened for study participation. We examined a) the percentage of patients considered eligible for video-delivered consultation, b) clinicians’, parents’ and patients’ satisfaction with video consultation, c) clinicians’ ratings of goal attainment in video consultation, and d) factors associated with satisfaction and goal attainment. 59% of the screening sample (n = 621) fulfilled eligibility criteria and were considered eligible for video consultation. A total of 267 patients consented to participate in the study and received a video consultation. Clinicians reported high levels of satisfaction with video consultation and high levels of goal attainment in video consultations, especially for patients scheduled for initial patient assessments. Parents and patients were also highly satisfied with the video consultations, especially if patients had less severe emotional and behavioral problems. The present findings suggest that video consultations are a feasible and well-accepted alternative to in-person consultations in child and adolescent mental health care, especially for children with less severe symptoms and for children in early phases of assessment and treatment. Limitations include the lack of a control group. The study was registered at the German Clinical Trials Registry (DRKS00023525).
Gesehen am 25.11.2024